Polypeptide-participating complex nanoparticles with improved salt-tolerance as excellent candidates for intelligent insulin delivery. Issue 23 (2nd March 2017) - Li, Yuqiang; Zhang, Yunyan; Yang, Junjiao; Yang, Jing
Abstract : The strategy of introducing synthetic polypeptides with hierarchical ordered structures into glucose-responsive materials is reported in this study to achieve self-regulated release of insulin under physiological salt concentration. Abstract : A facile strategy toward improving the salt-tolerance of a glucose-responsive delivery system to realize self-regulated release of insulin in a physiological environment (0.15 M phosphate buffer solution, pH 7.4 and 37 °C) is reported in this study. A type of glucose-responsive complex nanoparticle (CNP) is fabricated by co-assembly of two types of amphiphilic copolymers, poly(ethylene glycol)- block -poly(2-phenylboronic ester-1, 3-dioxane-5-ethyl)methylacrylate (MPEG- b -PPBDEMA) and poly(ethylene glycol)- block -poly(γ-benzyl-l -gluamate) (MPEG- b -PBLG). With the help of circular dichroism (CD) and FTIR, it is found that the highly ordered structures (α-helix and β-sheet) affected the stability of CNPs in 0.15 M salt concentration. The CNPs with 75% weight fraction of MPEG- b -PBLG exhibit self-regulated release of insulin in response to changes in the glucose concentration under physiological conditions, enabling the repeated on–off release of insulin regulated by normoglycemic and hyperglycemic levels. The probable mechanism of the controllable responsiveness is reasonably deduced based on an investigation of the change of the secondary structure of CNPs during the process of insulin release.